Potential Effects of Coronaviruses on the Liver: An Update - Wang, Xinyi; Lei, Jianyong; Li, Zhihui; Yan, Lunan (Frontiers in Medicine, 2021)
The coronaviruses that cause notable diseases, namely, severe acute respiratory syndrome (SARS), middle east respiratory syndrome (MERS) and coronavirus disease 2019 (COVID-19), exhibit remarkable similarities in genomic components and pathogenetic mechanisms. Although coronaviruses have widely been studied as respiratory tract pathogens, their effects on the hepatobiliary system have seldom been reported. Overall, the manifestations of liver injury caused by coronaviruses typically involve decreased albumin and elevated aminotransferase and bilirubin levels. Several pathophysiological theories have been proposed, including direct damage, immune-mediated injury, ischemia and hypoxia, thrombosis and drug hepatotoxicity. The interaction between pre-existing liver disease and coronavirus infection has been illustrated, whereby coronaviruses influence the occurrence, severity, prognosis and treatment of liver diseases. Drugs and vaccines used for treating and preventing coronavirus infection also have hepatotoxicity. Currently, the establishment of optimized therapy for coronavirus infection and liver disease comorbidity is of significance, warranting further safety tests, animal trials and clinical trials.